Regulasi Sebagai Pengontrol dalam Mendukung Investasi Pembangunan Infrastruktur di Indonesia dengan Skema Hak Pengelolaan Terbatas di Atas Barang Milik Negara - Widyaningrum Widyaningrum (LPPM Universitas Ekasakti Padang, 2023)
Legal certainty is one of the aspects that can attract investors to invest in Indonesia, one of which is investment in infrastructure development. This investment is one form of funding other than the state budget to develop Indonesia. One of the schemes as an alternative funding for infrastructure development is Limited Cooperation for Infrastructure Financing (KETUPI) which until now has not been able to be implemented, one of the obstacles is the covid pandemic, so to attract investors it is necessary to improve regulations and harmonize other regulations in the context of implementing this KETUPI. The role of regulation is very important, one aspect that provides legal certainty is the substance of the law itself, so that existing regulations need to contain the spirit contained in investment, namely equal treatment, openness and one-stop service for various investment pilots.